A CONTRIBUTION TO SLAVERY DEBATE: DOMESTIC LABOR OF MIGRANT CHILDREN IN FOCUS - Herceg Pakšić, Barbara (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Slavery and connected practices are ostensibly forgotten phenomenons, often considered they belong to the past. However, the migrant movements are placing focus on these forbidden practices and they are getting new features. The purpose of this paper is to (re)consider specific cases, those with European Court of Human Rights epilogue, where children were victims. Taking into account contemporary considerations on slavery and related practices we question the outcome analyzing key elements related to slavery notion. Emphasis is placed on insufficiently functional definitions in this area, the uncertainity of assessment criteria and comparison to judgments made by other courts. Considering that European Convention of Human Rights is described as the most powerful human rights protection mechanism with great impact on national (criminal) law systems, we search to see how the Convention ban is brought to life, analyze recent developments in this area, offering a different perspective to slavery notion. Keywords: Slavery, Servitude, Children, European Convention of Human Rights, Domestic Labour.